ANTIOXIDANT ACTIVITY OF ETHANOL EXTRACTS AND FRACTIONS KETEPENG CINA LEAVES(Cassia alata) WITH ABTS Assay - Danang Raharjo; Nur Hidayah; Kusumaningtyas Siwi Artini (Proceeding of International Conference on Science, Health, And Technology, 2022)
Antioxidants are compounds that have a molecular structure that can donate electrons to free radical molecules and can break the chain reaction of free radicals. This research was conducted to analyze the flavonoid content in the ethanol extract of ketepeng cina leaves and to determine the antioxidant activity of the ethanol extract and the fraction of the ketepeng cina leaves. This research is an experimental descriptive study. Ketepeng cina leaves were extracted using 96% ethanol, then partitioned using the liquid-liquid partition method. Flavonoid levels were determined using UV-VIS spectrophotometry at a wavelength of 435 nm. Antioxidant activity test using the ABTS method at a wavelength of 740 nm. The results showed that the flavonoid content of the ethanol extract of the ketepeng cina leaves was 11,054 ± 0.228 QE. The results of the antioxidant activity test of the ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction with IC50 values ​​were 23,709 ppm, 106,598 ppm, 14,534 ppm, and 49,844 ppm, respectively. The highest antioxidant activity was indicated by the ethyl acetate fraction with an IC50 value of 14,534 ppm with very strong activity